The Role of Traditional Betengan Games in Shaping Students' Social Character - Manullang, Jujur Gunawan; Junaidi, Ilham Arwan; Akhbar, M. Taheri (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Purpose.This study aims to determine the development of children's character formation by using traditional betengan games. Materials and Methods. This research method is qualitative with a descriptive type of research. The subject of the study was students of SMP Negeri 7 Palembang, the number of students was 27 children. Data collection techniques are carried out through observation, documentation and interviews. Data analysis techniques are carried out with percentage and descriptive techniques to obtain qualitative data. Result. the average recapitulation results of the percentage from the first week to the third week In the discipline aspect, the highest percentage was found in the Medium (S) category (59.26%), while the lowest percentage was found in the Very High (ST) category (0%). In terms of hard work, the highest percentage is in the High (T) category at 44.44%, while the lowest percentage is in the Low (R) category at 0%. In terms of honesty, the highest percentage is in the High (T) category of 44.44%, while the lowest percentage is in the Low (R) category of 0%. Conclusion. From the data from the results of the study, it can be concluded that there is a relationship between the role of traditional games and the formation of children's characters. The traditional game of Betengan has a significant role in shaping the social character of students. These activities involve direct interaction between players, teamwork, and collective strategies to achieve goals.